(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The main issues relating to the etiology, epidemiology and pathogenesis of measles infection are outlined. A classification of measles, features of its clinical course in children in terms of age are presented, characteristics of the clinical forms of the disease with damage to the central nervous system are given, and complications of measles are described. The features of the formation of immunity in measles are shown. Issues related to the laboratory and differential diagnosis of this infection are outlined, modern approaches to the treatment and specific prevention of measles are presented in detail, and the need for vaccination within the framework of the National Preventive Vaccination Calendar is emphasized. The requirements for carrying out anti-epidemic measures in the outbreak of measles and dispensary observation of children who have had measles infection are considered.